1995
DOI: 10.1071/wf9950237
|View full text |Cite
|
Sign up to set email alerts
|

Fire Growth in Grassland Fuels

Abstract: The development of grass fires originating from both point and line ignitions and burning in both open grasslands and woodlands with a grassy understorey was studied using 487 periods of fire spread and associated fuel, weather and fire-shape observations. The largest fires travelled more than 1000 m from the origin and the fastest 2-minute spread rate was over 2 m s-1. Given continuous fuel of uniform moisture content, the rate of forward spread was related to both the wind speed and the width of the head fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
120
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 0 publications
14
120
1
4
Order By: Relevance
“…1 describes the spread rate of line-ignited, ~10-m wide fires propagating over a distance of ~10 m, which for radiation-driven fires under calm or weak winds is expected to mirror the spread rate of larger fires (Wotton et al 1999). Experimental burning programs in grassland, woodland and forest in Australia have shown that the potential rate of forward fire spread increases with head fire width (up to 50-300 m) until reaching an asymptote determined by wind speed (Cheney & Gould 1995, Gould et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…1 describes the spread rate of line-ignited, ~10-m wide fires propagating over a distance of ~10 m, which for radiation-driven fires under calm or weak winds is expected to mirror the spread rate of larger fires (Wotton et al 1999). Experimental burning programs in grassland, woodland and forest in Australia have shown that the potential rate of forward fire spread increases with head fire width (up to 50-300 m) until reaching an asymptote determined by wind speed (Cheney & Gould 1995, Gould et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The by [11]. Their experiments, which were conducted in grasslands, showed that a fire may developed in a step-wise pattern with increases rate of spread being associated with shifts in wind direction and with a wider effective head fire.…”
Section: Time History Of the Fire Frontmentioning
confidence: 99%
“…Hence, the most relevant data available in the literature for field experiments such as the fire front shape, curvature and width cannot be used to validate the simulation of such models. Cheney et al [10,11] have however identified fire front shape as a significant variable influencing fire spread, which must be taken into consideration when using experimental fires to validate models. Then, caution should be exercised when those models predict rate of spread since it highly depends on shape and size of the fire front under wind and slope conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case 10 -Cheney et al [27] performed some experiments with large grassland fires over several years in Australia. Assuming that each vegetal stratum was reasonably similar, we applied our models.…”
mentioning
confidence: 99%